Interpretation and application of the 1999 Montreal convention arising from air carrier liability in Ghanaian courts : the case of Dr RSD Tei and Evelyn Jumbo v Messrs Ceiba Intercontinental - Hobe, Stephan (University of Pretoria, 2023)
Dissertation (LLM (International Law))--University of Pretoria, 2022.